Pombo, Antón. (2018). Guia do Caminho Português de Santiago (1ª edição). Santiago de Compostela: Através, 291 pp. - Lopes, Inês Americano (Limite. Revista de estudios portugueses y de la lusofonía, 2022)
recensión